(untitled) (Pain medicine, 2016)
The toxicity of Local Anesthetics is still the important problem of anesthesiology. The modern opinions of mechanisms of action and toxicity of Local Anesthetics are considered in the review. The special points of cardiopulmonary resuscitation in patients with Local Anesthetic intoxication and methods of prevention this complications are discussed.